The Special Antifungal Properties of Sugar Beet Leaves Against Fungal Species - Shojaei, Sa'adat; Lotfali, Ensieh; Kamalinejad, Mohammad (Novelty in Biomedicine, 2025)
Background: Research on antifungal agents for infectious diseases caused by multidrug-resistant microorganisms, particularly in immunocompromised patients, has continued. Mucormycosis, candidiasis, aspergillosis, and cryptococcosis are mortal and need more attention due to their spreading potential. Natural products with long-time usage as preservatives, food additives, and medicine in traditional and local resources have been investigated for too many purposes. Some medicinal herbs show antimicrobial properties. This study focused on the antifungal properties of Sugar beet (Beta vulgaris subsp. vulgaris), Yarrow (Achillea wilhelmsii K. Koch), Cinnamon (Cinnamomum zeylanicum), and Den or Don (Oliveria decumbens Vent.) against Candida albicans, Cryptococcus neoformans, Mucor circinelloides, and Aspergillus flavus. Materials and Methods: The minimum inhibitory concentration (MIC) of hydroethanolic crude extract of Sugar beet leaves (Beta vulgaris subsp. vulgaris), aerial parts of Yarrow (Achillea wilhelmsii K. Koch), Cinnamon barks (Cinnamomum zeylanicum), and Den or Don aerial parts (Oliveria decumbens Vent.) against clinical and standard isolates of Candida albicans, Cryptococcus neoformans, Mucor circinelloides, and Aspergillus flavus, determined according to CLSI M60 and CLSI-M38-A2 for yeasts and filamentous strains, respectively in comparison to Fluconazole and Amphotericin B as positive controls. Results: Sugar beet extract revealed the best minimum inhibitory concentration (MIC) values against clinical/standard Candida albicans (1 µg/ml and 0.5 µg/ml), respectively, but was insufficient against other species. Other herbal extracts showed a higher MIC range compared to controls. Conclusion: These findings suggest more research in in-vivo studies, finding safe herbal products with antifungal properties.